PERLINDUNGAN HUKUM DATA PRIBADI DALAM PERJANJIAN PINJAMAN ONLINE: Legal Protection of Personal Data in Online Loan Agreements - Alvina Rahim; Hetty Hassanah (Res Nullius Law Journal, 2026)
In online loan transactions, the consent of a third party as the owner of the contact details is often required. This consent is crucial because it demonstrates that the third party is conscious of and accepts the possibility of a breach of contract by the borrower. However, borrowers often use other people's personal data to be listed as emergency loan contacts on the internet without the data owner's permission. Analyzing the type of legal protection for personal data is the aim of this study on emergency contacts listed unilaterally in online loan agreements in accordance with "Law Number 27 of 2022 concerning Personal Data Protection" (PDP Law). With an emphasis on literature reviews and an examination of pertinent laws and legal sources, this study employs a descriptive analytical method with a normative juridical approach. Analyzing data uses qualitative juridical methods to obtain relevant legal conclusions. This study shows that legal protection includes the rights of data subjects to obtain information, give consent, withdraw consent, and file objections and legal claims for data misuse. There are three ways to enforce the law: administratively, civilly, and criminally. The research recommendations emphasise the significance of educating the public about personal data rights and available legal remedies.